DEVELOPING TALENT EXCELLENCE IN HIGHER LEARNING INSTITUTIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 9 May 2017 – “Local universities need to be bold in taking the steps to have a more inclusive and supportive promotional development exercise for its academicians,” said the ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail today in her welcoming remarks at the University Transformation Programme (UniTP) Orange Book Northern Zone Roadshow earlier today.